Exploring the sustainability of single use plastics in the biopharmaceuticals sector: a scoping review of challenges, opportunities, and impacts - Goggin, Malcolm; Fleming, Adrienne; MacMahon, Cormac; Owende, Philip (Frontiers in Sustainability, 2025)
Single-use plastics (SUPs) are synonymous with the biopharmaceuticals sector, facilitating economies of scale, process efficiency, flexibility and sterility assurance, all with a seemingly negligible environmental footprint. Yet, in ever-tightening regulation, mandated by the Sustainable Development Goals (SDGs) and by concern for large-scale industrial impacts, the sustainability of SUP consumption is increasingly being questioned. Whilst the sector contributes to human welfare, its transition risk is unlikely to remain immune to societal pressure for more sustainable production. This article aims to present a scoping review of the apparent contradiction between sectoral SUP adoption and the increasing importance of circularity. The approach to the review relies on three interwoven strands of evidence: [i] the intersectionality of sustainability policy and regulation with biopharmaceuticals, [ii] single-use technology in biopharmaceuticals and its impacts, and [iii] applications of circular economy principles to single-use technology. It is argued that, whilst life-cycle analysis (LCA) of SUPs in biopharmaceuticals articulates an environmental benefit vis-à-vis conventional technology, high energy intensity and embodied carbon in stainless steel renders the comparison redundant. Moreover, there is a dearth of evidence on circularity, post-use, and on end-of-life considerations. Likewise, there appears to be little sector-wide appetite for the adoption of embryonic solutions for enhancing circularity, such as biodegradables, carbon offsets, reusability, waste-to-energy, and ocean cleanup. Urgent mission-driven research is required on LCA, circular business model feasibility, materials innovation, regulatory frameworks, and sectoral-wide impact. A design-driven inquisition of their interactions, based on industrial symbiosis, could inform potential adoption pathways.